Efektivitas Bioakumulator Tanaman Hydrilla verticillatapadaCemaran Tanah pada Budi Daya Padi Genangan - Iqbal Bayu Ferdiansah; Mohammad Ubaidillah (Jurnal Ilmu Pertanian Indonesia, 2023)
Soil pollution can occur due to agricultural waste, one of which is the excessive use of pesticides. Contaminants that are often found are heavy metal of copper (Cu). Rice plants will absorb and store heavy metal elements in polluted soil and waters, and these heavy metals will undergo a process of bioaccumulation in plants that affect plant growth. Efforts to deal with heavy metal contaminants have been carried out. In its application, plants such as hydrilla plant (Hydrilla verticillata) can be used to reduce pollution in the environment. This study aims to determine the effectiveness of using hydrilla plants in reducing heavy metal pollutant copper in flooded rice cultivation. This research was conducted from May-November 2022 at the Agrotechnology Greenhouse, and for laboratory testing it was carried out at the CDAST Laboratory, University of Jember. This research was conducted using a completely randomized design consisting of one factor with four replications. Giving hydrilla did not significantly affect the morphology of rice plants but had a significant effect on the increasing levels of chlorophyll. The concentration of copper in rice plants decreased after treatment with hydrilla plants compared to negative controls without hydrilla plants. In this study, it can be concluded that the use of hydrilla was able to reduce the levels of copper metal present in rice plants and did not affect the growth of rice plants morphologically. Keywords: copper, hydrilla, paddy, soil contamination